THE INFLUENCE OF SATISFACTION TOWARD LOYALTY AND BUSINESS BUILDING OF MULTILEVEL MARKETING SALESPERSON IN ORIFLAME SURABAYA - Mei Retno A (Journal of Economics, Business, and Accountancy Ventura, 2010)
It is a fact that any product categorized as a daily need and therefore, it is considered the first product in the customer’s hand. The key to such a condition is by increasing the custom- ers’ loyalty to the product. To do so, multi-level-marketing (MLM) can be implemented in a business. This research attempts to see the influence of the variables such as communication satisfaction, marginal satisfaction, and product satisfaction, Loyalty to salesperson, Product Loyalty, and Business Builder toward the customers’ loyalty to the product. The author uses semantic scale differential as variable scale. The respondents as the subjects studied are the active members of Oriflame multilevel marketing company which have joined the company for at least 1 (one) year. There are 112 members taken as the sample and it uses Sstructural Equa- tion Mmodeling (SEM) to analyze the data. It was found that the  product satisfaction factor have positive influence toward the loyalty to product, the loyalty to product has also positive influence toward the loyalty to salesman and  the business builders. Next hypothesis say they marginal satisfaction has positive influence toward the loyalty to product, marginal satisfac- tion has positive influence toward the loyalty to salesman, and  communication satisfaction factor has positive influence toward the loyalty to salesman all are not accepted. Key words: Communication Satisfaction, Marginal Satisfaction, Product Satisfaction, Loy- alty to Salesperson, Product Loyalty, Business Builders.